2021
DOI: 10.1021/acs.iecr.1c02907
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology to Evaluate Solvent Extraction-Based Processes Considering Techno-Economic and Environmental Sustainability Criteria for Biorefinery Applications

Abstract: Extraction processes are widely used in biorefinery applications to recover target products from biomass, and their comprehensive evaluation is key to improving their economic and environmental sustainability. This paper applies a systematic methodology that combines a rigorous process design, techno-economic analysis, and life cycle assessment to evaluate the sustainability performance of solvent extraction-based processes, with a focus on downstream activities. The methodology, which consists of seven iterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 95 publications
(362 reference statements)
0
28
0
Order By: Relevance
“…21,42 The solvent-to-dry-feed-mass ratio is assumed to be 5:1, based on the study of Davis et al, 27 who reported commercial lipid recovery over 90% from wet algae biomass (20% dry weight). Also, modeling studies by Zapata-Boada et al 52 show that the solvent-to-feed ratio does not significantly affect triolein recovery from wet algae biomass (20% dry weight) when the mass ratio is above 3. The EXTRACT model in Aspen Plus is used to simulate the extraction column.…”
Section: ■ Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…21,42 The solvent-to-dry-feed-mass ratio is assumed to be 5:1, based on the study of Davis et al, 27 who reported commercial lipid recovery over 90% from wet algae biomass (20% dry weight). Also, modeling studies by Zapata-Boada et al 52 show that the solvent-to-feed ratio does not significantly affect triolein recovery from wet algae biomass (20% dry weight) when the mass ratio is above 3. The EXTRACT model in Aspen Plus is used to simulate the extraction column.…”
Section: ■ Methodologymentioning
confidence: 99%
“…To compare solvents’ performance, it is assumed that a countercurrent extraction column with five stages is needed to extract lipids from algae biomass, based on the study of Stephenson et al The temperature and pressure for the extraction process are assumed to be 25 °C and 101.325 kPa, respectively, which are typical values for algae lipid extraction. , The solvent-to-dry-feed-mass ratio is assumed to be 5:1, based on the study of Davis et al, who reported commercial lipid recovery over 90% from wet algae biomass (20% dry weight). Also, modeling studies by Zapata-Boada et al show that the solvent-to-feed ratio does not significantly affect triolein recovery from wet algae biomass (20% dry weight) when the mass ratio is above 3.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, indicators that understand the impact on the environment, health, and safety (HSE) must be considered . Another important indicator in solvent selection is process indicators, usually obtained from process simulators such as Aspen Plus . However, including these separation processes in commercial simulators requires an initial knowledge of the thermodynamic, physicochemical, and transport properties of the mixtures .…”
Section: Introductionmentioning
confidence: 99%
“…26 Another important indicator in solvent selection is process indicators, usually obtained from process simulators such as Aspen Plus. 27 However, including these separation processes in commercial simulators requires an initial knowledge of the thermodynamic, physicochemical, and transport properties of the mixtures. 28 Then, the experimental validation of the predictions made by the models of the behavior of real multicomponent mixtures is the first stage when designing new separation processes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For instance, life cycle assessment (LCA) and the environmental management tool can be used as a process design tool if implemented at early design stages . While there are several sustainability studies on biotechnological processes reported in the literature, these have mostly focused on biodiesel production , and high value-added chemicals derived from microalgae such as red anti-oxidant carotenoid astaxanthin , and β-carotene . Nevertheless, costing evaluations and LCA studies on colorant production from fungi cultures have been lacking.…”
Section: Introductionmentioning
confidence: 99%